ANOMALY CRUST FIELDS FROM MAGSAT SATELLITE MEASUREMENTS: THEIR PROCESSING AND INTERPRETATION - Rotanova N.M.; Kharitonov A.L.; Frunze A.Kh. (My University, 2004)
The space distribution of the magnetic anomaly field for the Pacific Ocean is obtained from data of the satellite MAGSAT. A number of long-wavelength magnetic anomalies of the region are identified. A spectrum analysis of a number of profiles of the anomaly field is performed disclosing typical scales of such anomalies. The wave transform of the anomaly magnetic profiles reveals and explicitly exposes the structure of the considered profile. A schematic complex cross-section is constructed, which demonstrates that the satellite data may be used in the study of the magnetic anomaly.